Experimental and Density Functional Theory Corroborated Optimization of Durable Metal Embedded Carbon Nanofiber for Oxygen Electrocatalysis - Ha, Yoonhoo; Kang, Sinwoo; Ham, Kahyun; Lee, Jaeyoung; Kim, Hyungjun (The journal of physical chemistry letters, 2019)
There is a growing need for widespread deployment of hydrogen and fuel cell technology for the realization of a sustainable energy landscape. However, due to the high price of platinum (Pt) catalysts, it is necessary to develop highly active and stable non-Pt oxygen reduction reaction (ORR) catalysts. Here, we describe a rational design of nonnoble metal-embedding and nitrogen-containing carbon nanofiber (M-CNF) catalysts. Using a combined experimental and computational approach, we establish an ORR activity volcano of M-CNF using the work function of the embedded metal as the descriptor. Near the top of the activity volcano, the embedded metal is further optimized by tuning the Fe1–x Co x alloy composition to simultaneously achieve high catalytic activity and durability. This work identifies the mechanistic importance of controlling the charge transfer between the metal and carbon layers, providing guidance for the design of non-Pt ORR catalysts using stable carbon-layer-protected metals.